A SYSTEMATIC LITERATURE REVIEW ON AR-RAHNU - Muhammad Ridzuan Abdul Aziz; Abidah Saad; Suraya Ika Tamrin; Suriana Ramli; Nor Shahrul Nizam Muhamad Nor (International Journal of Accounting, Finance and Business, 2023)
The purpose of this study is to identify the trends in the previous research conducted on ar-rahnu. This study employed systematic literature review on ar-rahnu on Scopus database. This study includes 15 journal articles from among 22 documents retrieved from the Scopus database. It is found that questionnaire survey was widely used in studying ar-rahnu. Diverse variables have been studied, mainly in testing independent variable-dependent variable relationships. Almost all of the studies were conducted in Malaysia, and mainly covered only certain parts of the country. Limited theories have been used in justifying the relationships in past studies. The findings from this paper can provide the basis in conducting future studies on ar-rahnu.